A Germinoma Involving Basal Ganglia: Case Report. Issue 1 (February 2016) - Yuebing, Xie; Anqi, Xiao; Xiang, Wang; Chao, You; Jing, Chen
Abstract : The central nervous system germinoma, as a malignant tumor, mainly occurs in the pineal gland region or hypothalamic area, and tends to involve adolescents. Germinoma occurring in the basal ganglia is very easy to be mistaken as other pathologic tumors because of its relative occurrence and atypical imaging performance. Here we report the case of a young man suffering from an atypical germinoma and discuss its differential diagnosis in imaging.